2022
DOI: 10.3390/en15228602
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Implementation for Health-Care Facilities in Developing and Underdeveloped Countries: Overview, Opportunities, and Challenges

Abstract: Developing and underdeveloped countries face innumerable problems related to the accessibility and quality of energy that put the lives of patients, health-care infrastructures, and health workers at risk. Current approaches, such as grid power, unsustainable energy sources such as diesel or gas, and mobile health clinics, have proven insufficient to address this issue. In response, access to reliable health care and electricity has undergone multiple transformations in the last decade, especially in remote an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…A comprehensive analysis by the World Health Organization (WHO) found that switching from fossil fuels to renewable energy could prevent millions of premature deaths annually by reducing air pollution-related illnesses . Furthermore, research has shown that investments in renewable energy infrastructure can create significant health savings by averting the healthcare costs associated with treating pollutionrelated diseases (Soto et al, 2022). In addition to mitigating air pollution, renewable energy adoption can also address other environmental health concerns, such as water contamination and land degradation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…A comprehensive analysis by the World Health Organization (WHO) found that switching from fossil fuels to renewable energy could prevent millions of premature deaths annually by reducing air pollution-related illnesses . Furthermore, research has shown that investments in renewable energy infrastructure can create significant health savings by averting the healthcare costs associated with treating pollutionrelated diseases (Soto et al, 2022). In addition to mitigating air pollution, renewable energy adoption can also address other environmental health concerns, such as water contamination and land degradation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Sittig et al (2022) conducted to provide suggestions for providing political and technical strategic approaches by addressing the increasing developments and resource use in health services. Soto et al (2022) mentioned the difficulties of applying solar energy in health centers. These challenges have been found to be operational, environmental, and economic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to reducing reliance on fossil fuels, renewable energies provide countless benefits such as higher grid reliability and flexibility, reduced emissions, and widespread access in remote areas and affordability has also been added to these benefits due to technological advances in recent years [5][6][7]. In addition to the mentioned cases, it is very necessary and vital to mention that today's human society has no choice but to move in the direction of clean and renewable energies due to severe climate changes and its severe paralyzing changes on daily life, although the cost of investing in such technologies is higher than the energy obtained from fossil fuels.…”
Section: Introductionmentioning
confidence: 99%